Additional financing and its forms and provisions: An applied study in Saudi banks / Mohammed Khalil M. Alshaikhi - Mohammed, Khalil, M. Alshaikhi (2018)
This study deals with additional financing, its forms and their legal description and the Shariah rules applied to it. The existing problem dealt with here consists in that noncompliance with the Shariah rules in these types of financing could lead to dilemmas and negative impacts that can only be avoided through compliance with the rules and regulations which in turn will make it efficient and positive. The researcher attempts to introduce the additional financing and its types and also to show its position in the people life in addition to emphasising the importance of following the Islamic teaching in the light of the Shariah objectives in these types of finance. The methods of personal additional financing from the financer bank or other and its applications in the Saudi banks will also be discussed in order to clarify its rules and regulations in the Shariah. The researcher is also going to talk about the real estate additional financing programme and explain the types of financing that the banks offer in order to arrive to its rules and regulations. In order to achieve these goals, the researcher applies the inductive method in collecting the research materials and the descriptive method in discussing the issues. The author also applies the analytical method to show the sense of the research and its dimensions as well as the applied method to examine financing concept in a real environment in the studied country, Kingdom of Saudi Arabia. All the above was to approach the subject from a the integral approach which the writer used to reach the following results: the existence of an obligation to pay the first debt or any portion of it from the additional financing invalidates the transaction, (2) non-delivering the goods to the customer could affect the transaction, (3) combination of the two contracts of real estate additional financing is acceptable even they are opposite because the financers are separated. The researcher recommends the Islamic financial institutions to avoid anything that can deceptively oblige the customer to pay the debt from the outcome of the additional financing and also strengthen the alternative product financing such as postponing settlement of additional financing till the payment of the fundamental financing made and support such product. The institutions are also advised to harmonise profit and non-profit services to achieve the Islamic objectives, benefit people and establish the Shariah in the land .